2018
DOI: 10.1371/journal.pone.0192910
|View full text |Cite
|
Sign up to set email alerts
|

The impact of “Option B” on HIV transmission from mother to child in Rwanda: An interrupted time series analysis

Abstract: BackgroundNearly a quarter of a million children have acquired HIV, prompting the implementation of new protocols—Option B and B+—for treating HIV+ pregnant women. While efficacy has been demonstrated in randomized trials, there is limited real-world evidence on the impact of these changes. Using longitudinal, routinely collected data we assessed the impact of the adoption of WHO Option B in Rwanda on mother to infant transmission.MethodsWe used interrupted time series analysis to evaluate the impact of Option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Many studies worldwide showed that the adoption of Option B+ had contributed to a decrease in the rate of MTCT of HIV. 16,[25][26][27][28][29] During the 12-year follow-up of this cohort, of 229 women who were on ART before or during pregnancy, only one child (0.43%) whose mother received AZT monotherapy (Option A) had HIV-positive at the age of 18 months. This finding is consistent with the study of Kesho Bora Group; they found that the mothers who received AZT monotherapy were less effective in PMTCT than those receiving triple ARV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies worldwide showed that the adoption of Option B+ had contributed to a decrease in the rate of MTCT of HIV. 16,[25][26][27][28][29] During the 12-year follow-up of this cohort, of 229 women who were on ART before or during pregnancy, only one child (0.43%) whose mother received AZT monotherapy (Option A) had HIV-positive at the age of 18 months. This finding is consistent with the study of Kesho Bora Group; they found that the mothers who received AZT monotherapy were less effective in PMTCT than those receiving triple ARV.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies worldwide showed that the adoption of Option B+ had contributed to a decrease in the rate of MTCT of HIV. 16 , 25 29 …”
Section: Discussionmentioning
confidence: 99%
“…The shifts toward universal HIV testing in antenatal care and immediate initiation on treatment for those who test positive, as recommended in the Option B+ policy, have significantly decreased rates of mother-to-child transmission of HIV [1,2]. This success has been facilitated by increases in the identification and enrollment of HIV positive pregnant women into HIV care [15,21].…”
Section: Discussionmentioning
confidence: 99%
“…Early initiation of antiretroviral therapy (ART) during pregnancy, followed by lifelong adherence to treatment, has shown to be effective in preventing mother-to-child transmission of HIV (PMTCT) and improving maternal health outcomes [1,2]. This clinical protocol, referred to as Option B+, was first recommended by the World Health Organization (WHO) in 2012 following successful implementation in Malawi [3].…”
Section: Introductionmentioning
confidence: 99%
“…Rwanda has made remarkable strides in increasing the coverage of health facilities providing prevention of mother-to-child transmission (PMTCT) services. In 2012, it became one of the rst African countries to recommend the initiation of lifelong antiretroviral therapy (ART) in all pregnant women regardless of CD4 cell count (known as Option B+) 5 . By June 2019, 98% of health facilities were offering PMTCT services, 99% of pregnant women attended at least one antenatal care visit, and 96.9% of HIV-infected pregnant women received ART for PMTCT.…”
Section: Introductionmentioning
confidence: 99%